Reflexiones sobre el egoísmo psicológico (Ensayo) - Enrique Trejo Vega (Nóesis)
This paper will present some criticisms of the theory of psychological egoism, which states that all the motives that cause us to act ultimately were response to personal interests. The criticism begins by noting that only the motives are not enough to be consider, but the intentions and the responsibility that the agent states to prosecute an act as selfish must also be taken into account. On the other hand, an act that meets one's own interests is not considered sufficient to call it selfish: egoism, while referring to moral condemnation, self-interest does not suffer from this assessment; therefore, it is necessary to distinguish these terms. With intent to oppose this theory, that each of our actions express selfish motives and denies the possibility of an altruistic act, I present the following lines.